Coordinating macroprudential policies within the Euro Area: the case of Spain - Rubio, Margarita; Carrasco-Gallego, José A. (Elsevier, 2016)
In the aftermath of the global financial crisis, there is consensus on the need for macroprudential policies to promote financial stability. However, the optimal way to implement such policies in the Euro area is a question open to debate, given that countries have to coordinate. In this paper, we propose a two-country, two-sector monetary union dynamic stochastic general equilibrium model (DSGE) with housing to analyze the optimal implementation of macroprudential policies in the Euro area. Currently, Spain is the only country within the EU that has not established a macroprudential regulator. We use Spain as a natural experiment to study the effects of a lack of coordination in the use of macroprudential policies in the European Monetary Union (EMU). We focus on a particular macroprudential policy, a rule regarding the loan-to-value ratio, which responds countercyclically to credit booms. We find that such a policy is welfare enhancing for the Euro area. Nevertheless, if one country does not implement the policy, but the rest of the EMU does, as in the current situation with Spain, this country still yields some benefits as a result of its partners' implementation of the policy because it gains from a more stable financial system without incurring any output costs. However, if all Euro countries actively implement the policy, the welfare gains for all of them are larger.